The Efficacy of the AMKALA Method (Take Word Song) in Helping Pandemic Children Learn to Write Poetry - Moch. Sulchan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
The AMKALA technique of learning is a combined effort combining the approach of word shopping and the method of imagination suggestion. There has been no prior study on the AMKALA method's efficacy in teaching poetry at the high school level. As a result, it is required to undertake research to determine if the AMKALA approach is beneficial for teaching high school students to create poetry. Due to the fact that learning is not conducted face-to-face during this epidemic, it is possible to have challenges conducting an efficient learning program. The researcher is interested in determining the efficacy of the word shopping approach when combined with the imagination suggestion method from songs for teaching children to create poetry during the epidemic. The purpose of this research is to examine the efficacy of the AMKALA technique (take the word song) in teaching students at SMK AL BADAR to create poetry during the epidemic. This study was done at SMK AL BADAR. The study design was experimental with a pretest-posttest control group. This study examines two variables: (1) the independent variable, which takes the form of the